Hierarchical membranes with size-controlled nanopores from photofluidization of electrospun azobenzene polymer fibers. Issue 35 (23rd August 2017) - Kang, Hong Suk; Cho, Hyesung; Panatdasirisuk, Weerapha; Yang, Shu
Abstract : A hierarchical membrane consisting of precisely controlled nanopores on top of micropores is fabricated via photofluidization for oil-in-water emulsion separation. Abstract : Membranes with hierarchical architectures, where pores of different sizes are integrated in tandem, are of great interest for water/oil emulsion separation due to their potential for achieving large flux, high selectivity, and mechanical durability. However, it remains challenging to modify the pore size in the nanoscale without sacrificing the flux, thus limiting the size of the oil/water droplets that can be filtered. Here, we electrospin a thin layer of azobenzene polymer ( i.e., polydisperse orange 3, PDO 3) fibers on a highly porous supporting layer ( i.e., an electrospun fiber network from polycaprolactone), followed by photofluidization of PDO 3 fibers to shrink the pore size from micrometer to nanometer by controlling the light exposure dosage. We show that the fabricated hierarchical membranes can be utilized for the gravity driven separation of water-in-oil emulsion droplets with size as small as 50 nm while maintaining high flux ( ca. 15 000 L m −2 h −1 bar −1 for surfactant-free emulsions and ca. 1000 L m −2 h −1 bar −1 for surfactant-stabilized emulsions).